Problems of implementing Online learning for Teachers, Parents, and Students during the Covid 19 Pandemic - Ita, Efrida (Universitas Negeri Malang, 2023)
The implementation of online learning during the covid-19 pandemic is a challenge for teachers and parents of children. The purpose of this study is to describe the implementation of online learning during the covid 19 pandemic and the problems of implementing online learning for teachers, parents and children at PAUD Terpadu Citra Bakti during the covid 19 pandemic. The method used in this study was a case study method with the qualitative research approach. This study was done at PAUD Terpadu Citra Bakti, Ngada Regency, East Southeast Province for 3 (three) months starting with pre-research activities until the research was completed. The research subjects were parents, teachers and children of PAUD Terpadu Citra Bakti, while the object of research was the implementation of online learning and the problems of online learning during the covid 19 pandemic. The data collection method was done using interview and observation methods with interview guide instruments and observation guidelines. Data analysis through the stages of the Milles and Huberman model, namely data collection, data reduction, data presentation and drawing conclusions. The results show that the implementation of online learning was carried out through the use of google meet, zoom meetings, and learning videos produced by the teachers, but the learning process does not run optimally. In the implementation of the online learning process, there are problems got, namely related to the lack of learning facilities by most parents of children, android mobile phones or laptops, the cost and access to using android phones which are quite burdensome for parents, teachers' unpreparedness in aspects of learning methods and media, unpreparedness of parents in learning, learning assistance for children at home, the lack of parental understanding regarding online learning, and providing an assessment of children's learning outcomes.